Job satisfaction : a comparison of employees of recreation tourism companies in Iceland and employees in general - Þórunn Harðardóttir 1978- (2014)
This study was aimed at examining the job satisfaction of employees of recreation tourism companies in Iceland and comparing the results to employees in general. Study participants were 131 employees of 27 organizations and the instrument used for the comparison was the Icelandic Employee Index based on a database with answers from 5.813 respondents from 87 organizations collected from 2004 through 2013. Employees of tourism recreation companies generally reported higher satisfaction even though the global job satisfaction was not significantly higher. Nonetheless, employees of tourism recreation companies felt more satisfied than employees in general about the work, working conditions, and salary and benefits as well as rating higher on the image construct. Furthermore, more commitment was evident of employees of tourism recreation companies than employees in general. The findings indicate that employees of recreation tourism companies evaluate intrinsic rewards about their work as an important component of their job satisfaction. That gives administrators in the industry a hint of how to attract and retain the right talent to their organizations in order to keep up with the current and foretasted growth of tourism in Iceland.